Endometrial stromal sarcoma arising from polypoid endometriosis: Case report and literature review. (2020) - Carbone, Fabio; Kaur, Manou Manpreet; Chok, Aik Yong; Kontovounisios, Christos; Ind, Thomas; Rasheed, Shahnawaz
Highlights: This is a novel case of a 53 years old, nulliparous lady, who had been treated over a 10-year period for recurrent and symptomatic polypoid endometriosis of the pelvis. During this time, she underwent four surgical resections, the final one being a total pelvic exenteration, with histology demonstrating the presence of a rare myxoid low grade Endometrial Stromal Sarcoma (ESS) that had arisen in Polypoid Endometriosis (PE). Polypoid endometriosis is a rare and uncommon variant of endometriosis that may present as a polypoid mass that simulates a malignant neoplasm. Typically, PE develops locally as a large benign pelvic mass. However, it may sometimes conceal a malignant disease in its context. PE may involve different pelvic organs and can mimic a malignant mass in the pelvis. It mostly affects women in their peri- or post-menopausal age and it is not always related to hormonal therapy. Malignances, such as Endometrial Stromal Sarcoma in this case, can arise in the context of PE and their diagnosis can be challenging. Surgical excision may constitute radical multi-organ resection, particularly for recurrent and symptomatic cases. However, the recurrence rates after surgery can be significant. Histopathologic findings for Polypoid Endometriosis and Endometrial Stromal Sarcoma are well described in this article (in literature there is great lack of this information). Abstract: Background: Polypoid endometriosis (PE) is a rare and uncommon variant of endometriosis that may present as a polypoid mass that simulates a malignant neoplasm. Typically, PE develops locally as a large benign pelvic mass. However, it may sometimes conceal a malignant disease in its context. Case presentation: A 53 years old, nulliparous lady, had been treated over a 10-year period for recurrent and symptomatic polypoid endometriosis of the pelvis. During this time, she underwent four surgical resections, the final one being a total pelvic exenteration, with histology demonstrating the presence of a rare myxoid low grade Endometrial Stromal Sarcoma (ESS) that had arisen in PE. Conclusion: PE is a rare variant growth pattern of endometriosis which may involve different pelvic organs and can mimic a malignant mass in the pelvis. It mostly affects women in their peri- or post-menopausal age and it is not always related to hormonal therapy. Malignances, such as Endometrial Stromal Sarcoma in this case, can arise in the context of PE and their diagnosis can be challenging. Surgical excision may constitute radical multi-organ resection, particularly for recurrent and symptomatic cases. However, the recurrence rates after surgery can be significant.